(untitled) (Gadau Journal of Pure and Allied Sciences, 2024)
Typhoid fever is among the major prevalent disease in Nigeria due to various interconnected factors such as scarce amenities for handling unwanted products and abuse of antibiotics; these among other factors are responsible for the widespread of typhoid fever affecting both underage children and young adults. This study was a descriptive cross-sectional conducted from September to November, 2023. The study population consisted of adults female age ranged from 18 years and above. A pilot study was conducted which tested the validity and reliability of the instruments. The response rate was 100% for there were no non-consenting respondents. The study variables were independent and dependent. Data was analyzed using SPSS Computer software version 11. The processed data was presented in Tables, Pie chart; and Chi-square test of independence (contingency tables) was used to determine if there was a relationship between control measures of typhoid and it’s occurrence in the study area. The study revealed that those with low level of education suffered from typhoid more than those who had attained a higher level of education and therefore education played a key role in the prevalence of typhoid among pregnant women based on the study. It has been shown that the higher the level of education the more the typhoid prevalence decreased among the adults as in primary, secondary and college levels respectively. The findings of this study also showed that 63% of the pregnant women had suffered from typhoid fever in one or more times in their life time, and only 37% had not. This is a clear indication that typhoid fever is prevalent among pregnant women attending General hospital in Azare. The results showed that those with low level of education were more than 50% and they suffered from typhoid episodes in their lifetime more than those with higher level of education. This study revealed that 63% did not have water storage facility while 37% provided water storage facilities within their households. The results of the study found that 80.2% of the residents had temporary houses, 14.4% had semi-permanent houses and 5.4% had permanent houses. These statistics reveal that most of the residents were poor and that they were vulnerable to poor housing which could promote poor state of sanitation. Poor sanitation practices are a cause of bacterial, viral, protozoa, and helminthic infections. Similarly, on waste collection 82.9% were dissatisfied about it, and 17.1% were satisfied. The main reason of dissatisfaction on waste collection was that it was done unprofessionally (52.9%) and irregularly (36.3%). The majority (47.1%) of the residents of the area under study felt that the drainage systems posed a problem of leaking, 36% felt the problem with drainage was smell and 16.9% felt that drainage system were contaminating their surface water sources.